2015
DOI: 10.1002/14651858.cd010925.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for fatigue in Parkinson's disease

Abstract: Based on the current evidence, no clear recommendations for the treatment of subjective fatigue in PD can be provided. Doxepin may reduce the impact of fatigue on ADL and fatigue severity; however, this finding has to be confirmed in high quality studies. Rasagiline may be effective in reducing levels of physical fatigue in PD. No evidence was found for the effectiveness of levodopa-carbidopa, memantine, caffeine, methylphenidate, modafinil or exercise. Studies are needed to investigate the effect of exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 94 publications
2
36
0
Order By: Relevance
“…Evidence for the role of exercise in improving fatigue remains inconclusive. Similar to our results, a meta‐analysis of previous trials with exercise failed to show significant improvements in fatigue or QoL . Possible explanations for our findings include the program's emphasis on physical therapies, lack of regular follow‐up or carer support and co‐morbidities such as concomitant arthritis.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Evidence for the role of exercise in improving fatigue remains inconclusive. Similar to our results, a meta‐analysis of previous trials with exercise failed to show significant improvements in fatigue or QoL . Possible explanations for our findings include the program's emphasis on physical therapies, lack of regular follow‐up or carer support and co‐morbidities such as concomitant arthritis.…”
Section: Discussionsupporting
confidence: 84%
“…Assessments were performed by the clinic physiotherapist and an exercise physiologist. Assessment consisted of the following tests: (a) physical: fast gait velocity in metres/second over 10 m, distance in metres walked in 2 minutes (2MW), time in seconds taken to “Timed Up and Go” (TUG), number of “Sit To Stands” in 30 seconds (STS) and the Berg Balance Score (BBS); and b) psychosocial function (Parkinson's Disease Quality of Life Questionnaire (PDQ‐39), Depression, Anxiety, Stress Score (DASS‐21), and Parkinson's Fatigue Survey (PSF‐16) . These tests were conducted in the order listed.…”
Section: Methodsmentioning
confidence: 99%
“…This is encouraging as systematic reviews have not established improvements in this construct despite the improvements in motor symptoms 1 2. Certainly, while systematic reviews support that exercise interventions can benefit PwP and are safe,1 2 7 38 they also confirm that the longer term effects have not been established and that pragmatic delivery models are largely untested 3–6 39 40. We propose that the intervention provides evidence for effectively supporting PwP to engage with an exercise programme for 6 months through standard community resources.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with dopaminergic or other treatments in more advanced PD have been disappointing. In a recent review , it was concluded that so far there is insufficient evidence to support the treatment of fatigue in PD with any drug or non‐drug treatment. Our positive findings must be interpreted with caution, as patients who received agonists tended to be younger with less advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, the longitudinal development of fatigue has been studied mostly in selected patient groups, and the possible effect of medical treatment is unclear. Medications, including levodopa, dopamine agonists, monoamine oxidase B inhibitors, selective serotonin/serotonin‐norepinephrine reuptake inhibitors, amantadine and modafinil have all been hypothesized to influence the degree of fatigue experienced, but the evidence is scarce .…”
Section: Introductionmentioning
confidence: 99%